Relativistic electrons from sparks in the laboratory. Issue 6 (18th March 2016) - Østgaard, N.; Carlson, B. E.; Nisi, R. S.; Gjesteland, T.; Grøndahl, Ø.; Skeltved, A.; Lehtinen, N. G.; Mezentsev, A.; Marisaldi, M.; Kochkin, P.
Abstract: Discharge experiments were carried out at the Eindhoven University of Technology in 2013. The experimental setup was designed to search for electrons produced in meter‐scale sparks using a 1 MV Marx generator. Negative voltage was applied to the high voltage (HV) electrode. Five thin (1 mm) plastic detectors (5 cm 2 each) were distributed in various configurations close to the spark gap. Earlier studies have shown (for HV negative) that X‐rays are produced when a cloud of streamers is developed 30–60 cm from the negative electrode. This indicates that the electrons producing the X‐rays are also accelerated at this location, that could be in the strong electric field from counterstreamers of opposite polarity. Comparing our measurements with modeling results, we find that ∼300 keV electrons produced about 30–60 cm from the negative electrode are the most likely source of our measurements. A statistical analysis of expected detection of photon bursts by these fiber detectors indicates that only 20%–45% of the detected bursts could be from soft (∼10 keV) photons, which further supports that the majority of detected bursts are produced by relativistic electrons. Key Points: The majority of signals were produced by relativistic electrons accelerated to ∼300 keV 30–60 cm from the electrodes The first study that reports direct measurements of relativistic electrons from sparks in laboratory Important for how relativistic electrons are produced in the streamer zone ahead of leaders in lightning discharges in the atmosphere